Lament, Hospitality, and Living Together with ‘Our’ Children: Rethinking Religious Education in Local Churches with Children Who Have Refugee/IDP Backgrounds - Ku, Eliana Ah-Rum (Religious education, 2023)
This article explores how religious education can access and embrace children with refugee/internally displaced people (IDP) backgrounds to address the issues associated with feelings of loss safely and to contribute to a socially just framework. This article makes practical recommendations for religious educators to respond better to the suffering of children who experience violence, oppression, and control, and it invites the formation of communities of mutual respect that honor children’s identities and subjective experiences. Through the discourses and practice of lament and hospitality and with the ethics of inter-embracement, this article rethinks the meaning of a sense of social belonging, safety, and restoration.